Relationships Among Employee Perception of Their Manager’s Behavioral Integrity, Moral Distress, and Employee Attitudes and Well-Being - Prottas, David J. (2013)
Hypothesized relationships among reports by employees of moral distress, their perceptions of their manager’s behavioral integrity (BI), and employee reports of job satisfaction, stress, job engagement, turnover likelihood, absenteeism, work-to-family conflict, health, and life satisfaction were tested using data from the 2008 National Study of the Changing Workforce (n = 2,679). BI was positively related to job satisfaction, job engagement, health, and life satisfaction and negatively to stress, turnover likelihood, and work-to-family conflict, while moral distress was inversely related to those outcomes. The magnitudes of relationships with job satisfaction, job engagement, and life satisfaction were greater with BI than with moral distress. Moral distress mediated the relationships between BI and the employee outcomes, supporting the view that employee’s perceptions of their manager’s BI might influence the employee’s behaviors as well as their attitudes.
Keywords: Stress; Person–environment fit; Moral Distress; managerial ethics; Job engagement; Job satisfaction; Employee attitudes; Behavioral integrity